Unsustainable land use trajectories in the Tocantins/Araguaia basin: Insights from future scenario modeling - Schmitz, Marcelo Henrique; Malek, Žiga; do Couto, Edivando Vitor; Gentil, Eduardo; Cardozo, Ana Lúcia Paz; Moretto, Yara; da Silveira, Natália Stefanini [UNESP]; Agostinho, Angelo Antonio (Springer Nature, 2025)
Effective watershed management is essential for biodiversity conservation and mitigating environmental impacts like deforestation and ecosystem disruptions, especially in the context of climate change. The Tocantins/Araguaia Basin (TOAR), Brazil's second-largest watershed, faces significant challenges due to unsustainable land use practices. To address this, we modeled future land use and cover changes (2015–2045) using the CLUE model under three scenarios: Business-as-usual (BAUS), Conservation-based (CONS), and Production-based (PROD). Key drivers included soil type, average temperature, and yearly precipitation. Projections indicate persistent deforestation and habitat fragmentation, particularly under PROD, while CONS still projects notable losses in forests, savannas, and grasslands. These results highlight the urgent need for proactive conservation measures, stricter environmental regulations, and sustainable land use planning to protect TOAR’s ecosystems and biodiversity. Addressing these issues is critical for preserving this vulnerable and understudied region amidst growing environmental pressures.
Keywords: Amazon; Brazilian cerrado; Conservation; Public policy; Sustainability; Water resources